Degradable skin-friendly moisture-conducting corn fiber blended yarn material and preparation method thereof
Patent Information
- Application Number
- CN202611417420.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-14
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]针对现有技术的不足,本发明提供了一种可降解亲肤导湿的玉米纤维混纺纱材料及其制备方法,解决了现有玉米纤维与粘胶纤维混纺纱材料在纺织整理过程中存在的亲水导湿性能仍需改善、亲水整理耐洗性不足以及常规化学整理体系与玉米纤维材料皮肤接触安全性和可降解属性适配性不足的问题
1、本发明采用氯化胆碱、L-乳酸、L-乳酸钠和丙三醇组成的亲水复合体系,与聚(甲基乙烯基醚-交替-马来酸)、复配聚醚和六水合氯化镁共同形成水性整理液。该整理液在浸轧阶段能够较好地润湿聚乳酸/粘胶混纺纱线,并在热风排湿过程中形成较低水活度的浓缩状态。低水活度环境有利于聚(甲基乙烯基醚-交替-马来酸)在较低焙烘温度下实现整理剂表观固着,从而提高整理后纱线经水洗后的功能保持性;
Abstract
Description
Technical Field
[0001] This invention relates to the field of textile material processing technology, specifically to a biodegradable, skin-friendly, and moisture-wicking corn fiber blended yarn material and its preparation method. Background Technology
[0002] Polylactic acid (PLA) fiber, also known as corn fiber, is a synthetic fiber made from fermentable sugar sources or starchy raw materials such as corn, wheat, cassava, and sugarcane. Lactic acid is produced through fermentation, followed by polymerization and spinning. PLA fiber is bio-based and biodegradable, making it valuable in the textile industry. However, PLA fiber lacks sufficient hydrophilicity, and its water absorption and moisture-wicking properties can still be improved after being made into yarn or fabric.
[0003] In existing technologies, polylactic acid fibers are typically blended with viscose fibers, or hydrophilic finishing agents are used to impregnate and finish yarns and fabrics to improve their hydrophilic and moisture-wicking properties. However, simple blending has limited effect on improving liquid water conductivity; the finishing effect achieved by relying on the physical adsorption of surfactants or hydrophilic finishing agents is prone to decline after repeated washing, resulting in insufficient hydrophilic and moisture-wicking durability.
[0004] To improve finishing durability, existing processes also involve introducing chemical crosslinking agents or increasing baking temperatures. However, polylactic acid fibers are sensitive to hot, humid, acidic, and alkaline environments. Higher temperatures or unsuitable acidic or alkaline conditions can easily affect the yarn's mechanical properties. At the same time, the finishing solution can easily migrate with the moisture during the dehumidification process and accumulate on the yarn surface, resulting in uneven finishing, a rough hand feel, or increased difficulty in washing.
[0005] Therefore, this invention proposes a biodegradable, skin-friendly, and moisture-wicking corn fiber blended yarn material and its preparation method to overcome the shortcomings of the prior art. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this invention provides a biodegradable, skin-friendly, and moisture-wicking corn fiber blended yarn material and its preparation method. This solves the problems of existing corn fiber and viscose fiber blended yarn materials in the textile finishing process, such as the need to improve the hydrophilic and moisture-wicking properties, insufficient washability of hydrophilic finishing, and insufficient compatibility of conventional chemical finishing systems with the skin contact safety and biodegradability of corn fiber materials.
[0007] To address the above problems, the present invention provides the following technical solution.
[0008] In a first aspect, the present invention provides a biodegradable, skin-friendly, and moisture-wicking corn fiber blended yarn material, employing the following technical solution: A biodegradable, skin-friendly, and moisture-wicking corn fiber blended yarn material, wherein the biodegradable, skin-friendly, and moisture-wicking corn fiber blended yarn material is made by impregnating corn fiber blended yarn with a finishing solution, removing moisture, and baking; wherein the corn fiber is polylactic acid fiber.
[0009] Based on the preparation of 1L of final finishing solution, the finishing solution contains the following components: choline chloride 18-22g; L-lactic acid 20-25g; sodium L-lactic acid 4-6g; glycerol 5-8g; poloxamer 188 9-12g; thermally responsive cloud point adjusting block copolymer 3-4g; poly(methyl vinyl ether-alternative-maleic acid) aqueous solution, wherein the mass fraction of the poly(methyl vinyl ether-alternative-maleic acid) aqueous solution is 10wt%-15wt%, and the amount added is such that the PMVE / MA content, calculated on a dry basis based on the anhydride-type PMVE / MA raw material, is 25-35g; magnesium chloride hexahydrate 3-5g; and deionized water to a final volume of 1L.
[0010] The thermally responsive cloud point regulating block copolymer is selected from polyoxypropylene-polyoxyethylene-polyoxypropylene type reverse triblock copolymer, or from medium cloud point polyoxyethylene-polyoxypropylene-polyoxyethylene type triblock copolymer.
[0011] By employing the above technical solution, choline chloride, L-lactic acid, sodium L-lactic acid, and glycerol together form a hydrophilic composite system with buffering and low water activity regulating effects. After the finishing solution is immersed in the yarn, this system helps improve the wetting and diffusion state of the polylactic acid / viscose blended yarn and reduces the water activity of the system during subsequent moisture removal, providing favorable conditions for the apparent fixation of poly(methyl vinyl ether-alternating-maleic acid) at a lower baking temperature.
[0012] Poloxamer 188 is combined with a thermally responsive cloud point regulating block copolymer to form a complex polyether system. When heated to the pre-distribution temperature range, the complex polyether system undergoes turbidity, resulting in a controlled deposition of the finishing components on the inner and outer surfaces of the yarn. This reduces the tendency of the finishing solution to migrate towards the yarn surface with moisture during subsequent moisture removal. This process improves the hydrophilic uniformity of the finished yarn along its length, while also ensuring anti-pilling and anti-water droplet absorption properties.
[0013] Magnesium chloride hexahydrate is used as a catalyst in the finishing solution to promote low-temperature fixation. During the drying process after dehumidification, the carboxyl groups in poly(methyl vinyl ether-alternating-maleic acid) react with the hydroxyl groups in viscose fibers under low water activity conditions to undergo esterification fixation. This reaction can be represented by the following formula: R-COOH+R'-OH→R-COO-R'+H2O; In the formula, R-COOH represents the carboxyl group on the poly(methyl vinyl ether-alternating-maleic acid) molecular chain, and R'-OH represents the hydroxyl group in viscose fiber, or the hydroxyl group provided by the hydroxyl-containing component in the finishing system. The above reaction is beneficial to improving the apparent fixation rate of the finishing agent on the yarn, thereby enhancing the functional retention of the finished material after multiple washes.
[0014] Preferably, the corn fiber blended yarn is a blended yarn of polylactic acid fiber and viscose fiber, and the mass ratio of polylactic acid fiber to viscose fiber is 65-75:25-35.
[0015] By adopting the above technical solution, polylactic acid (PLA) fibers provide a biodegradable fiber matrix and certain mechanical support for the blended yarn, while viscose fibers provide hydroxyl reaction sites and a hydrophilic base. Controlling the mass ratio of PLA fibers to viscose fibers within the aforementioned range helps to achieve a balance between yarn mechanical properties, hydrophilicity, and finishing agent fixation efficiency.
[0016] Preferably, the thermally responsive cloud point regulating block copolymer is a polyoxypropylene-polyoxyethylene-polyoxypropylene type reverse triblock copolymer; the average molecular weight of the reverse triblock copolymer is 1800-2200, the mass fraction of polyoxyethylene segments is 45wt%-55wt%, it is liquid at room temperature, and its cloud point is 65-73℃ when measured alone.
[0017] Preferably, the thermally responsive cloud point regulating block copolymer is a polyoxyethylene-polyoxypropylene-polyoxyethylene type intermediate cloud point triblock copolymer; the intermediate cloud point triblock copolymer has an average molecular weight of 1800-2200, a polyoxyethylene segment mass fraction of 45wt%-55wt%, is liquid at room temperature, and has a cloud point of 70-75℃ when measured alone.
[0018] By adopting the above technical solution, the thermally responsive turbidity point regulating block copolymer can adjust the turbidity behavior of the compounded polyether system to the temperature range used in the high-humidity pre-distribution step, ensuring that the finishing solution remains uniform during the low-temperature padding stage and undergoes turbidity deposition during the heated pre-distribution stage. This setting helps to reduce the degree of migration of finishing components to the outer layer of the yarn during direct hot air dehumidification, thereby improving the finishing uniformity.
[0019] Preferably, based on the preparation of 1L of final finishing solution, the finishing solution comprises the following components: 20g choline chloride, 22g L-lactic acid, 5g sodium L-lactic acid, 6g glycerol, 10g poloxamer 188, 4g thermally responsive cloud point adjusting block copolymer, 250g of 12wt% poly(methyl vinyl ether-alternative-maleic acid) aqueous solution, 4g magnesium chloride hexahydrate, and deionized water to a final volume of 1L.
[0020] By adopting the above technical solution, the hydrophilic composite system, the compounded polyether system, poly(methyl vinyl ether-alternating-maleic acid), and magnesium chloride hexahydrate in the finishing solution are within a relatively coordinated dosage range. This ratio is beneficial for obtaining lower water activity, suitable turbidity temperature, and higher apparent fixation rate of the finishing agent, while reducing the impact of excessive acidic components, salts, or free hydrophilic agent residues on yarn hand feel and subsequent processing adaptability.
[0021] Preferably, the poly(methyl vinyl ether-alternating-maleic acid) aqueous solution is prepared by the following steps: Poly(methyl vinyl ether-alternating-maleic anhydride) powder was divided into five equal batches. Under mechanical stirring conditions of 250–400 r / min, each batch of poly(methyl vinyl ether-alternating-maleic anhydride) powder was added sequentially to deionized water. After the previous batch of poly(methyl vinyl ether-alternating-maleic anhydride) powder was wetted by deionized water and there was no floating dry powder or obvious agglomerates, the next batch of poly(methyl vinyl ether-alternating-maleic anhydride) powder was added. After all five batches of poly(methyl vinyl ether-alternating-maleic anhydride) powder were added, stirring was continued for 10 min to obtain a suspension. The suspension is heated to 85–95°C in a covered but not sealed container, and the temperature is maintained at 85–95°C while stirring continuously at a speed of 250–400 r / min for 2–4 hours to hydrolyze and open the anhydride groups; heating is stopped when the suspension becomes a homogeneous solution with no visible solid particles, no visible flocs and no stratification. The homogeneous solution was cooled to 25°C at a stirring speed of 100–200 r / min. The total mass of the homogeneous solution was weighed, and deionized water was added to make up to the predetermined total mass. The solution was filtered through a filter screen and allowed to stand to remove bubbles until no visible bubbles were visible, thus obtaining the poly(methyl vinyl ether-alternative-maleic acid) aqueous solution.
[0022] By adopting the above technical solutions, batch feeding and controlled stirring rate can reduce the formation of agglomerates when acid anhydride powder comes into contact with water, allowing the powder to gradually wet and enter a hydrolytic state. Hydrolysis at 85–95°C is beneficial for the anhydride groups to open rings and form carboxyl-containing structures. A covered but not sealed operation reduces excessive water evaporation and avoids pressure buildup caused by sealed heating. The steps of replenishing the total mass, filtration, and degassing help obtain a stable concentration and uniform appearance of poly(methyl vinyl ether-alternating-maleic acid) aqueous solution.
[0023] Secondly, the present invention provides a method for preparing a biodegradable, skin-friendly, and moisture-wicking corn fiber blended yarn material, employing the following technical solution: A method for preparing a biodegradable, skin-friendly, and moisture-wicking corn fiber blended yarn material includes the following steps: S1. Prepare all the raw materials required for preparing the finishing solution, mix the raw materials to prepare the finishing solution, and adjust the pH value of the finishing solution to 3.6-4.0; S2. The corn fiber blended yarn to be treated is immersed in the finishing solution and subjected to a two-dip and two-padding process. The liquid content of the corn fiber blended yarn is controlled to be 65% to 75% to obtain the padded yarn. S3. The impregnated yarn is introduced into a temperature and humidity control zone for humidity control and dwell treatment to obtain pretreated yarn. S4. The pretreated yarn is introduced into a hot air drying room for hot air penetration treatment to remove moisture, and the dehumidified yarn is obtained. S5. After dehumidification, the yarn is directly introduced into the baking oven without intermediate washing and baked at 115-125℃ for 3-4 minutes to obtain the baked yarn. S6. The baked yarn is washed, neutralized, rinsed and dried to obtain a biodegradable, skin-friendly and moisture-wicking corn fiber blended yarn material.
[0024] By employing the above technical solutions, the pH value of the finishing solution is controlled at 3.6–4.0, maintaining a weakly acidic reaction environment in the finishing system. The two-dip, two-nip process, combined with a 65%–75% liquid carry-over rate, facilitates the uniform distribution of the finishing solution in the yarn. The controlled-humidity dwell treatment allows the compounded polyether system to undergo thermal response distribution under low water loss conditions, reducing the degree of concentration and migration of finishing components to the yarn surface during subsequent dehumidification stages. Hot air penetration dehumidification controls the residual free water in the yarn to a suitable range, ensuring the finishing system reaches a low water activity concentrated state before baking. Low-temperature baking at 115–125℃ improves the apparent fixation rate of the finishing agent and reduces the impact of higher-temperature baking on the mechanical retention of polylactic acid fibers. Subsequent washing, neutralization washing, and rinsing steps remove free acids, salts, and unbonded water-soluble residues.
[0025] Preferably, step S1 is implemented as follows: Choline chloride, L-lactic acid, sodium L-lactic acid, and glycerol are added sequentially to deionized water and stirred until homogeneous. The pH of the first mixture is then adjusted to 3.6–4.0 using an aqueous solution of L-lactic acid or sodium L-lactic acid to obtain the second mixture. Poloxamer 188 and thermally responsive cloud point adjusting block copolymer were added to the second mixture and stirred until homogeneous. Then, an aqueous solution of poly(methyl vinyl ether-alternating-maleic acid) was added to obtain the third mixture. Magnesium chloride hexahydrate was pre-dissolved in deionized water to prepare an aqueous solution of magnesium chloride. The aqueous solution of magnesium chloride was injected into the third mixture at a rate of 10 mL / min using a peristaltic pump at 25°C with continuous stirring. Stirring was continued and deionized water was added to bring the volume to 1 L to obtain the finishing solution.
[0026] By adopting the above technical solution, a hydrophilic composite system consisting of choline chloride, L-lactic acid, sodium L-lactic acid, and glycerol is first prepared, and then the polyether component and poly(methyl vinyl ether-alternating-maleic acid) aqueous solution are added, which helps maintain the homogeneity of the finishing solution. Magnesium chloride hexahydrate is added last in the form of a dilute aqueous solution, and the addition rate is controlled, which helps reduce the risk of early complexation, thickening, flocculation, or precipitation of magnesium ions with carboxyl or carboxyl groups in poly(methyl vinyl ether-alternating-maleic acid) under local high concentration conditions.
[0027] Preferably, in step S3, the ambient temperature of the temperature and humidity control zone is controlled at 63-68°C, the relative humidity is controlled at 90%-95%, the residence time is 45-60s, and the water loss of the yarn after padding in the temperature and humidity control zone is controlled to be 8%-12% of the initial liquid content of the yarn after padding.
[0028] By adopting the above technical solution, the high humidity environment reduces the rapid water loss of the yarn after padding in the initial stage of heating, and the ambient temperature of 63-68℃ keeps the compounded polyether system within the thermal response turbidity temperature range. The combination of temperature, humidity and residence time is conducive to completing the pre-distribution under low water loss conditions, thereby improving the hydrophilicity uniformity and anti-migration effect of the finished yarn.
[0029] Preferably, in step S4, the processing temperature of the hot air drying chamber is 90-95°C, and the yarn is taken out of the hot air drying chamber when the free water content of the yarn after dehumidification drops to 5%-8% calculated on a dry basis.
[0030] By adopting the above technical solution, hot air penetration treatment removes some of the free water in the yarn, allowing the finishing components to enter a concentrated state. Controlling the residual free water content at 5%–8% is beneficial for balancing the flowability of the finishing components and the low water activity fixation environment: when the residual free water is too low, the flowability of the finishing components decreases; when the residual free water is too high, the water activity of the system increases, which is not conducive to obtaining a high apparent fixation rate of the finishing agent under low-temperature baking conditions.
[0031] Preferably, step S6 is implemented as follows: After baking, the yarn is rinsed with deionized water at 35°C for 1 minute, then immersed in a sodium bicarbonate aqueous solution at 35°C, pH 7.0 and mass concentration of 0.2-0.5 g / L for 2 minutes, rinsed with deionized water at 25°C for 60 seconds, and dried at 80-90°C.
[0032] By employing the above technical solution, 35°C deionized water rinsing is used to remove loosely bound water-soluble adsorbates from the yarn surface; sodium bicarbonate aqueous solution washing is used to adjust residual acidic components and reduce the risk of low pH value in the finished yarn water extract; 25°C deionized water rinsing is used to further remove soluble salts and small molecule residues. These washing, neutralization, and rinsing steps help improve the removal of water-soluble residues from the finished yarn, skin contact safety, and adaptability to subsequent processing.
[0033] This invention provides a biodegradable, skin-friendly, and moisture-wicking corn fiber blended yarn material and its preparation method. It has the following beneficial effects: 1. This invention employs a hydrophilic composite system composed of choline chloride, L-lactic acid, sodium L-lactic acid, and glycerol, which, together with poly(methyl vinyl ether-alternating-maleic acid), compounded polyether, and magnesium chloride hexahydrate, forms an aqueous finishing solution. This finishing solution effectively wets polylactic acid / viscose blended yarns during the padding stage and forms a concentrated state with low water activity during hot air dehumidification. The low water activity environment facilitates the apparent fixation of the finishing agent (poly(methyl vinyl ether-alternating-maleic acid)) at a lower baking temperature, thereby improving the functional retention of the finished yarn after washing. 2. This invention employs a compound of poloxamer 188 and a thermally responsive turbidity point regulating block copolymer to maintain a uniform state of the finishing solution during the low-temperature padding stage and induce turbidity within the high-humidity pre-distribution temperature range. Through high-humidity temperature-controlled dwell treatment, the migration of finishing components in the yarn is regulated, reducing the degree to which finishing components migrate with moisture to the yarn surface during direct hot air dehumidification. This process helps improve the hydrophilic uniformity of the finished yarn along its length and enhances the fabric's anti-pilling and anti-fuzzing properties while maintaining a shorter water droplet wetting time. 3. This invention controls the residual free water content after hot air dehumidification to 5%–8% on a dry basis and employs a low-temperature baking process at 115–125℃. This free water control range takes into account both the flowability of the finishing components and the low water activity fixation environment, which is beneficial to improving the apparent fixation rate of the finishing agent; at the same time, the lower baking temperature reduces the risk of mechanical property degradation of polylactic acid fibers in a hot, humid, and acidic environment, enabling the finished yarn to maintain a high breaking strength retention rate and polylactic acid viscosity-average molecular weight retention rate; 4. This invention does not add formaldehyde-based crosslinking agents. After standard water washing, the pH value of the water extract of the finished material is within the corresponding limit range for textile products that come into direct contact with the skin. Free and hydrolyzed formaldehyde and decomposable carcinogenic aromatic amine dyes were not detected, and the odor evaluation result was odorless. The above results can serve as auxiliary evidence for the material's skin contact safety and physicochemical skin affinity. The corn fiber blended yarn material uses polylactic acid fiber and viscose fiber as the main base materials, which, while achieving hydrophilic and moisture-wicking finishing, helps to maintain the material's biodegradable properties and subsequent processing adaptability. Detailed Implementation
[0034] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0035] The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Except for polymer raw materials, block copolymers and textile substrates, all small molecule reagents not specifically mentioned are commercially available analytical grade or higher products.
[0036] Poly(methyl vinyl ether-alternating-maleic anhydride) is an alternating copolymer formed from methyl vinyl ether and maleic anhydride, abbreviated as PMVE / MA, with CAS number 9011-16-9. The repeating unit of the anhydride type PMVE / MA can be represented as (C3H6O·C4H2O3). n After hydrolysis or partial hydrolysis, the maleic anhydride units are partially or completely converted into carboxyl-containing structures. The PMVE / MA used in the embodiments of this invention is a hydrolyzed or partially hydrolyzed product. Unless otherwise specified, its dosage is based on the dry basis of the anhydride-type PMVE / MA raw material, with a weight-average molecular weight of 1.0 × 10⁻⁶. 6 Up to 1.2×10 6 .
[0037] Poloxamer 188 is a nonionic triblock copolymer of polyethylene oxide, polypropylene oxide, and polyethylene oxide, commonly known as Pluronic F68, with CAS number 9003-11-6. The average molecular weight of Poloxamer 188 is 7680 to 9510, and the mass fraction of polyethylene oxide segments is 75% to 85%, preferably 80%.
[0038] The reverse triblock copolymer is a polyoxypropylene-polyoxyethylene-polyoxypropylene type block copolymer with CAS number 9003-11-6. This CAS number is a general category number for block copolymers and is not used to distinguish specific varieties. This reverse triblock copolymer has an average molecular weight of 1800 to 2200, a polyoxyethylene segment mass fraction of 45% to 55%, and is liquid at room temperature. In the examples, a reverse block copolymer with an average molecular weight of 2000, a polyoxyethylene segment mass fraction of 50%, and a cloud point of 69°C was used.
[0039] The triblock copolymer with medium or low cloud point is selected as a polyoxyethylene-polyoxypropylene-polyoxyethylene block copolymer with CAS number 9003-11-6, an average molecular weight of 1800 to 3500, and a polyoxyethylene segment mass fraction of 45% to 55%. In the examples, a variety with an average molecular weight of 1900, liquid at room temperature, and a cloud point of 73°C is used to adjust the spot temperature window to 60°C to 70°C.
[0040] The CAS number for choline chloride is 67-48-1; the CAS number for L-lactic acid is 79-33-4; sodium lactate is the sodium salt of L-lactic acid, with the CAS number 867-56-1; the CAS number for glycerol is 56-81-5; the CAS number for magnesium chloride hexahydrate is 7791-18-6; and the CAS number for sodium bicarbonate is 144-55-8.
[0041] The corn fiber referred to in this article is polylactic acid fiber with polylactic acid as the main component. This polylactic acid fiber is made by fermenting fermentable sugar sources or starchy raw materials such as corn, wheat, cassava, and sugarcane to obtain lactic acid, which is then polymerized and spun.
[0042] Polylactic acid and viscose fiber blended yarn is a conventional textile substrate. In the examples and comparative examples, a blended yarn with a polylactic acid fiber to viscose fiber mass ratio of 70:30 was used, and the same linear density, twist and pretreatment conditions were maintained.
[0043] Preparation Example 1: This preparation example provides a method for preparing an aqueous solution of poly(methyl vinyl ether-alternating-maleic acid), including the following steps: (1) Weigh 120g of poly(methyl vinyl ether-alternative-maleic anhydride) powder and divide it into five equal batches of 24g each; add 880g of deionized water into a container, turn on the mechanical stirrer and adjust the speed to 300 rpm; (2) Under stirring conditions of 300 rpm, the first batch of 24 g of poly(methyl vinyl ether-alternative-maleic anhydride) powder was slowly added to deionized water. After the powder was wetted by the aqueous phase and there was no floating dry powder or obvious agglomerates, the next batch of powder was added. The addition of five batches of powder was completed in sequence. After all five batches of powder were added, stirring was continued at 300 rpm for 10 minutes to obtain a suspension with a mass fraction of 12% based on the amount of anhydride-type raw material fed. (3) Heat the system to 90°C in a covered but not sealed container, maintain the temperature at 90°C and stir continuously at 300 rpm for 3 hours to hydrolyze and open the anhydride group; (4) After the system changes from a milky white suspension to a homogeneous solution with no visible solid particles, no visible flocs and no stratification, stop heating and cool to 25°C at a stirring speed of 150 rpm. (5) After cooling, weigh the total mass of the system, add deionized water to make up to 1000 g, then filter through a 150 mesh filter and let stand to remove bubbles until no visible bubbles are present, to obtain a poly(methyl vinyl ether-alternative-maleic acid) aqueous solution for later use.
[0044] Preparation Example 2: This preparation example provides a method for preparing an aqueous solution of poly(methyl vinyl ether-alternating-maleic acid), including the following steps: (1) Weigh 100g of poly(methyl vinyl ether-alternative-maleic anhydride) powder and divide it into five equal batches of 20g each; add 900g of deionized water into the container, turn on the mechanical stirrer and adjust the speed to 250 rpm; (2) Under stirring conditions of 250 rpm, the first batch of 20 g of poly(methyl vinyl ether-alternative-maleic anhydride) powder was slowly added to deionized water. After the powder was wetted by the aqueous phase and there was no floating dry powder or obvious agglomerates, the next batch of powder was added. The addition of five batches of powder was completed in sequence. After all five batches of powder were added, stirring was continued at 250 rpm for 10 minutes to obtain a suspension with a mass fraction of 10% based on the amount of anhydride-type raw material fed. (3) Heat the system to 85°C in a covered but not sealed container, maintain the temperature at 85°C and stir continuously at a speed of 250 rpm for 2 hours to hydrolyze and open the anhydride group; (4) After the system changes from a milky white suspension to a homogeneous solution with no visible solid particles, no visible flocs and no stratification, stop heating and cool to 25°C at a stirring speed of 100 rpm. (5) After cooling, weigh the total mass of the system, add deionized water to make up to 1000 g, then filter through a 150 mesh filter and let stand to remove bubbles until no visible bubbles are present, to obtain a poly(methyl vinyl ether-alternative-maleic acid) aqueous solution for later use.
[0045] Preparation Example 3: This preparation example provides a method for preparing an aqueous solution of poly(methyl vinyl ether-alternating-maleic acid), including the following steps: (1) Weigh 150g of poly(methyl vinyl ether-alternative-maleic anhydride) powder and divide it into five equal batches of 30g each; add 850g of deionized water to the container, turn on the mechanical stirrer and adjust the speed to 400 rpm; (2) Under stirring conditions of 400 rpm, the first batch of 30 g of poly(methyl vinyl ether-alternative-maleic anhydride) powder was slowly added to deionized water. After the powder was wetted by the aqueous phase and there was no floating dry powder or obvious agglomerates, the next batch of powder was added. The addition of five batches of powder was completed in sequence. After all five batches of powder were added, stirring was continued at 400 rpm for 10 minutes to obtain a suspension with a mass fraction of 15% based on the amount of anhydride-type raw material fed. (3) Heat the system to 95°C in a covered but not sealed container, maintain the temperature at 95°C and stir continuously at 400 rpm for 4 hours to hydrolyze and open the anhydride group; (4) After the system changes from a milky white suspension to a homogeneous solution with no visible solid particles, no visible flocs and no stratification, stop heating and cool to 25°C at a stirring speed of 200 rpm. (5) After cooling, weigh the total mass of the system, add deionized water to make up to 1000 g, then filter through a 100 mesh filter and let stand to remove bubbles until no visible bubbles are present, to obtain a poly(methyl vinyl ether-alternative-maleic acid) aqueous solution for later use.
[0046] Example 1: This example provides a method for preparing a biodegradable, skin-friendly, and moisture-wicking corn fiber blended yarn material, including the following steps: (1) Add 500 mL of deionized water to the mixing tank, then add 20 g of choline chloride, 22 g of L-lactic acid, 5 g of sodium L-lactic acid, and 6 g of glycerol in sequence. Turn on the mechanical stirrer and stir at 200 rpm for 10 minutes. Adjust the pH of the system to 3.8 using an aqueous solution of L-lactic acid or sodium L-lactic acid. Then add 10 g of poloxamer 188 and 4 g of reverse triblock copolymer, which is a variety with an average molecular weight of 2000, a polyoxyethylene segment mass fraction of 50%, and a cloud point of 69°C. Continue stirring at 200 rpm for 15 minutes until homogeneous. Add 250 g of the poly(methyl vinyl ether-alternating-maleic acid) aqueous solution obtained from Preparation Example 1. Dissolve 4 g of magnesium chloride hexahydrate in 50 mL of deionized water beforehand. With the mixing tank system temperature at 25°C and under continuous stirring, inject the magnesium chloride aqueous solution into the mixing tank at a rate of 10 mL per minute using a peristaltic pump. After adding the materials, continue stirring for 20 minutes, and check and confirm that the pH value of the system is 3.8. Add deionized water to make up to 1 liter to obtain the finishing solution. Sampling and testing showed that the finishing solution was a homogeneous liquid at 25°C, with no visible precipitation, flocculation, or stratification. When the finishing solution was sampled and heated to 65°C and held for 45 seconds, observable turbidity appeared. After cooling to 25°C, no irreversible flocculation or precipitation occurred. (2) The blended yarn of corn fiber, i.e. polylactic acid fiber and viscose fiber in a mass ratio of 70:30 is immersed in the above finishing solution and a two-dip and two-roll process is adopted. The pressure of the rolling mill is set to control the liquid carrying rate of the blended yarn to 70%. (3) The impregnated blended yarn is introduced into the temperature and humidity control zone and kept for 45 seconds under the conditions of ambient temperature of 65℃ and relative humidity of 92%. The moisture content of the yarn in this stage is 10% of the initial liquid content. (4) Lead the yarn out of the temperature and humidity control zone and into the hot air drying room. Perform hot air penetration treatment at 95°C. When the moisture detection device shows that the residual free water content of the yarn has dropped to 6%, lead the yarn out of the drying room. The residual free water content is calculated on a dry basis. (5) After the moisture is removed, the yarn is directly put into the baking oven without intermediate washing and baked at 120°C for 3 minutes; (6) After baking, the yarn is first washed with deionized water at 35°C for 1 minute, then immersed in sodium bicarbonate aqueous solution at 35°C, pH 7.0 and mass concentration of 0.3 g / L for 2 minutes, then rinsed with deionized water at 25°C for 60 seconds, and dried at 85°C to obtain the hydrophilic corn fiber blended yarn material.
[0047] Example 2: This example provides a method for preparing a biodegradable, skin-friendly, and moisture-wicking corn fiber blended yarn material, including the following steps: (1) Add 500 mL of deionized water to the mixing tank, then add 18 g of choline chloride, 20 g of L-lactic acid, 4 g of sodium L-lactic acid, and 5 g of glycerol in sequence. Turn on the mechanical stirrer and stir at 200 rpm for 10 minutes. Adjust the pH of the system to 3.6 using an aqueous solution of L-lactic acid or sodium L-lactic acid. Then add 9 g of poloxamer 188 and 3 g of reverse triblock copolymer, which is a variety with an average molecular weight of 2000, a polyoxyethylene segment mass fraction of 50%, and a cloud point of 69°C. Continue stirring at 200 rpm for 15 minutes until homogeneous. Add 250 g of the poly(methyl vinyl ether-alternating-maleic acid) aqueous solution obtained from Preparation Example 2. Dissolve 3 g of magnesium chloride hexahydrate in 50 mL of deionized water beforehand, and inject it into the mixing tank at a rate of 10 mL per minute while the mixing tank system temperature is 25°C and under continuous stirring. After adding the materials, continue stirring for 20 minutes to confirm that the pH value of the system is 3.6. Add deionized water to make up to 1 liter to obtain the finishing solution. Sampling and testing showed that the finishing solution was a homogeneous liquid at 25°C, with no visible precipitation, flocculation, or stratification. When the finishing solution was sampled and heated to 63°C and held for 50 seconds, observable turbidity appeared. After cooling to 25°C, no irreversible flocculation or precipitation occurred. (2) The blended yarn of corn fiber, i.e. polylactic acid fiber and viscose fiber in a mass ratio of 70:30 is immersed in the above finishing solution and a two-dip and two-nip process is adopted to control the liquid carrying rate to 65%. (3) The impregnated blended yarn is introduced into the temperature and humidity control zone and kept for 50 seconds under the conditions of ambient temperature of 63℃ and relative humidity of 90%. The yarn water loss is 8% of the initial liquid content. (4) Draw the yarn out and introduce it into the hot air drying room, where it undergoes hot air penetration treatment at 90°C. When the residual free water content of the yarn drops to 8%, it is drawn out of the drying room. The residual free water content is calculated on a dry basis. (5) Directly introduce the dehumidified yarn into the baking oven and bake at 115℃ for 4 minutes; (6) After baking, the yarn is washed with deionized water at 35°C for 1 minute, then immersed in sodium bicarbonate aqueous solution at 35°C, pH 7.0 and mass concentration of 0.2 g / L for 2 minutes, rinsed with deionized water at 25°C for 60 seconds, and dried at 80°C to obtain corn fiber blended yarn material.
[0048] Example 3: This example provides a method for preparing a biodegradable, skin-friendly, and moisture-wicking corn fiber blended yarn material, including the following steps: (1) Add 500 mL of deionized water to the mixing tank, then add 22 g of choline chloride, 25 g of L-lactic acid, 6 g of sodium L-lactic acid, and 8 g of glycerol in sequence. Stir at 200 rpm for 10 minutes, and adjust the pH of the system to 4.0 using an aqueous solution of L-lactic acid or sodium L-lactic acid. Then add 12 g of poloxamer 188 and 4 g of a reverse triblock copolymer with an average molecular weight of 2000, a polyoxyethylene segment mass fraction of 50%, and a cloud point of 69°C. Continue stirring at 200 rpm for 15 minutes until homogeneous. Add 233.3 g of the poly(methyl vinyl ether-alternating-maleic acid) aqueous solution obtained from Preparation Example 3. Dissolve 5 g of magnesium chloride hexahydrate in 50 mL of deionized water beforehand, and inject it into the mixing tank at a constant rate of 10 mL per minute while the system temperature is 25°C and continuous stirring is maintained. Continue stirring for 20 minutes, confirm the pH value of the system is 4.0, add deionized water to make up to 1 liter, and obtain the finishing solution. Sampling and testing showed that the finishing solution was a homogeneous liquid at 25℃, with no visible precipitation, flocculation or stratification; after heating the sample of the finishing solution to 68℃ and holding it at that temperature for 40 seconds, observable turbidity appeared, and no irreversible flocculation or precipitation occurred after cooling to 25℃. (2) The blended yarn of corn fiber, i.e. polylactic acid fiber and viscose fiber in a mass ratio of 70:30 is immersed in the above finishing solution and a two-dip and two-nip process is adopted to control the liquid content to 75%. (3) The impregnated yarn is introduced into the temperature and humidity control zone and kept for 60 seconds under the conditions of ambient temperature of 68°C and relative humidity of 95%. The yarn water loss is 12% of the initial liquid content. (4) The yarn is introduced into a hot air drying oven and subjected to hot air penetration treatment at 95°C until the residual free water content is reduced to 5%. The residual free water content is calculated on a dry basis. (5) Directly introduce the dehumidified yarn into the baking oven and bake at 125°C for 3 minutes; (6) The baked yarn is rubbed with deionized water at 35°C for 1 minute, then immersed in a sodium bicarbonate aqueous solution at 35°C, pH 7.0 and mass concentration of 0.5 g / L for 2 minutes, rinsed with deionized water at 25°C for 60 seconds, and then dried at 90°C to obtain corn fiber blended yarn material.
[0049] Example 4: This example provides a method for preparing a biodegradable, skin-friendly, and moisture-wicking corn fiber blended yarn material, including the following steps: (1) Add 500 mL of deionized water to the mixing tank, then add 20 g of choline chloride, 22 g of L-lactic acid, 5 g of sodium L-lactic acid, and 6 g of glycerol in sequence. Stir at 200 rpm for 10 minutes, and adjust the pH of the system to 3.8 using an aqueous solution of L-lactic acid or sodium L-lactic acid. Then add 10 g of poloxamer 188 and 4 g of a medium-turbidity triblock copolymer. The copolymer selected is a polyoxyethylene-polyoxypropylene-polyoxyethylene block copolymer with an average molecular weight of 1900, which is liquid at room temperature and has a cloud point of 73°C when measured separately. Continue stirring at 200 rpm for 15 minutes until homogeneous. Add 250 g of the poly(methyl vinyl ether-alternating-maleic acid) aqueous solution obtained from Preparation Example 1. Dissolve 4 g of magnesium chloride hexahydrate in 50 mL of deionized water beforehand, and inject it into the mixing tank at a rate of 10 mL per minute while the system temperature is 25°C and stirring is continuous. Continue stirring for 20 minutes, confirm the pH value of the system is 3.8, add deionized water to make up to 1 liter, and obtain the finishing solution. Sampling and testing showed that the finishing solution was a homogeneous liquid at 25℃, with no visible precipitation, flocculation, or stratification; after heating the sample of the finishing solution to 67℃ and holding it at that temperature for 45 seconds, observable turbidity appeared, and no irreversible flocculation or precipitation occurred after cooling to 25℃. (2) The blended yarn of corn fiber, i.e. polylactic acid fiber and viscose fiber in a mass ratio of 70:30 is immersed in the finishing solution and a two-dip and two-nip process is adopted to control the liquid carrying rate to 70%. (3) The impregnated yarn is introduced into the temperature and humidity control zone and kept for 45 seconds under the conditions of ambient temperature of 67°C and relative humidity of 92%. The yarn water loss is 10% of the initial liquid content. (4) The yarn is introduced into a hot air drying oven and subjected to hot air penetration treatment at 95°C until the residual free water content is reduced to 6%. The residual free water content is calculated on a dry basis. (5) Directly introduce the dehumidified yarn into the baking oven and bake at 120°C for 3 minutes; (6) The baked yarn is rubbed with deionized water at 35°C for 1 minute, then immersed in sodium bicarbonate aqueous solution at 35°C, pH 7.0 and mass concentration of 0.3 g / L for 2 minutes, rinsed with deionized water at 25°C for 60 seconds, and then dried at 85°C to obtain corn fiber blended yarn material.
[0050] Comparative Example 1: Compared to Example 1, the difference lies in that the reverse triblock copolymer is not added in the preparation step of the finishing solution, and the amount of poloxamer 188 is increased from 10 grams to 14 grams, so that the total amount of polyether is the same as in Example 1. Sampling and testing showed that the finishing solution was a homogeneous liquid at 25°C, with no visible precipitation, flocculation, or stratification; after heating to 65°C and holding for 60 seconds, no observable turbidity appeared. All other conditions were the same as in Example 1.
[0051] Comparative Example 2: Compared with Example 1, the difference is that the temperature and humidity control zone dwell step is omitted, and the impregnated blended yarn is directly introduced into a 95°C hot air drying room for hot air penetration treatment, and the residual free water content of the yarn is controlled to be 6% at the end of hot air dehumidification. The other conditions are the same as in Example 1.
[0052] Comparative Example 3: Compared to Example 1, the difference lies in that the hot air penetration treatment in the hot air drying oven is performed with an extended hot air dehumidification time, reducing the residual free water content of the blended yarn to 0.8% when it exits the drying oven. The residual free water content is calculated on a dry basis. All other conditions are the same as in Example 1.
[0053] Comparative Example 4: Compared to Example 1, the difference lies in that the hot air penetration treatment in the hot air drying oven is performed with a shorter hot air dehumidification time, so that the free water residue of the blended yarn is 18% when it exits the drying oven. The free water residue is calculated on a dry basis. All other conditions are the same as in Example 1.
[0054] Comparative Example 5: Compared to Example 1, the difference is that choline chloride is not added in the preparation of the finishing solution, and deionized water is added to bring the volume to 1 liter, maintaining the final pH of the system at 3.8. All other conditions are the same as in Example 1.
[0055] Comparative Example 6: Compared to Example 1, the difference is that glycerol is not added in the preparation of the finishing solution, and deionized water is added to bring the volume to 1 liter, maintaining the final pH of the system at 3.8. All other conditions are the same as in Example 1.
[0056] Comparative Example 7: Compared with Example 1, the difference is that in the baking step, the baking oven temperature is adjusted from 120°C to 150°C, and the baking time is adjusted from 3 minutes to 1.5 minutes. All other conditions are the same as in Example 1.
[0057] Comparative Example 8: Compared to Example 1, the difference lies in that L-lactic acid and sodium L-lactic acid are not added in the preparation step of the finishing solution. Instead, a 10% hydrochloric acid aqueous solution is used to adjust the final system pH to 3.8, and deionized water is added to bring the volume to 1 liter. All other conditions are the same as in Example 1.
[0058] Comparative Example 9: Compared to Example 1, the difference lies in the method of adding magnesium chloride hexahydrate in the preparation step of the finishing solution. Specifically, after adding the poly(methyl vinyl ether-alternating-maleic acid) aqueous solution, instead of pre-dissolving the magnesium chloride hexahydrate into an aqueous solution and injecting it using a peristaltic pump, 4 grams of magnesium chloride hexahydrate are added to the solution tank in solid powder form all at once. The remaining conditions are the same as in Example 1.
[0059] Test Example 1: Test objective: To evaluate the turbidity temperature range of the compound polyether dispensing agent system and to investigate the effect of the addition method of magnesium chloride hexahydrate on the viscosity stability and appearance stability of the working solution.
[0060] The experimental steps are as follows: The working solutions prepared in Example 1, Comparative Example 1, and Comparative Example 9 were selected as test objects. Transmittance testing was performed using fresh samples after each working solution was prepared and degassed; samples were left to stand for 24 hours for observation of rheological stability and appearance. Before instrument testing, each group of fresh samples was placed in a 25°C constant temperature water bath for 30 minutes to degauge, in order to reduce the interference of air bubbles on the transmittance test results. The wavelength of the UV-Vis spectrophotometer with temperature control was set to 600 nm. Appropriate amounts of the degassed working solutions were injected into standard cuvettes with a path length of 1 cm. A heating program was set to uniformly raise the sample temperature from 25.0℃ to 85.0℃ at a rate of 2.0℃ / min. The change in sample transmittance was recorded during the heating process. The temperature at which the transmittance decreased to 50% of the initial transmittance was taken as the turbidity temperature of the working solution. If the sample did not decrease to 50% of the initial transmittance within the test temperature range, the turbidity temperature was recorded as greater than 85.0℃. Rheological properties were tested using a rotational rheometer in conjunction with a coaxial cylindrical testing system. The tests were conducted at 25.0℃ and a shear rate of 10 s⁻¹. -1 Under the specified conditions, the apparent viscosity of each working solution was measured at 0, 6, 12, and 24 hours after preparation. The viscosity change value and viscosity change rate were recorded over 24 hours, and the presence of turbidity, stringing, flocculation, or precipitation was evaluated by visual observation.
[0061] The experimental results are shown in Table 1: .
[0062] As shown in Table 1, the turbidity temperature of the working solution in Example 1 was 64.7℃, which is within the temperature range used in the high-humidity pre-distribution step, and the transmittance decreased to 11.5% at 85℃. This result indicates that the polyether compound system in Example 1 can undergo turbidity during the heating process. Comparative Example 1 did not add the reverse triblock copolymer, and the amount of poloxamer 188 was increased to the same total polyether amount as in Example 1. It did not meet the turbidity criterion in the test range of 25.0℃ to 85.0℃, and the transmittance was still 83.1% at 85℃. The above results show that when poloxamer 188 is used alone, the working solution maintains a high transmittance in this test temperature range; after introducing the reverse triblock copolymer, the thermal response turbidity temperature of the polyether compound system was adjusted to the temperature range required by this process. Rheological test results showed that after standing at 25°C for 24 hours, the apparent viscosity of the working solution in Example 1 increased from 12.4 mPa·s to 12.9 mPa·s, with a viscosity change rate of 4.03%, while maintaining a uniform and transparent appearance. In Comparative Example 9, the method of adding magnesium chloride hexahydrate was changed. Solid magnesium chloride hexahydrate was added all at once to the system containing PMVE / MA. Its apparent viscosity increased to 46.3 mPa·s at 0 hours and further increased to 218.7 mPa·s after 24 hours, with the appearance of white cotton-like clumps. These results indicate that the form and method of adding magnesium chloride hexahydrate affect the rheological stability of the working solution; pre-preparing magnesium chloride hexahydrate into a dilute aqueous solution and slowly adding it under stirring conditions helps reduce the risk of early thickening and flocculation of the working solution. Based on the combined results of light transmittance, viscosity and appearance observation, the working fluid of Example 1 exhibits both thermal response turbidity behavior within the target temperature range and rheological stability under static conditions at 25°C; Comparative Example 1 mainly shows insufficient thermal response turbidity, and Comparative Example 9 mainly shows insufficient working fluid stability.
[0063] Test Example 2: Test objective: To evaluate the formation of a low water activity concentration environment in the yarn by the finishing components after hot air dehumidification to a specific free water residue level, and to investigate the effect of this environment on the fixation effect of PMVE / MA under low-temperature baking conditions.
[0064] The experimental steps are as follows: Yarns from Example 1, Comparative Examples 3, 4, 5, and 6, after hot air dehumidification and before entering the baking process, were used as test samples. The moisture content at the dehumidification endpoint was calculated on a dry basis, i.e., moisture content at the dehumidification endpoint = (mass of sample after dehumidification - mass of fully dried sample) / mass of fully dried sample × 100%. 5.00 grams of the test yarn were weighed and quickly placed in the sample dish of the water activity meter and sealed. After equilibration for 15 minutes, and once the reading change was no greater than 0.003 / min, the water activity measurement value at 25°C was recorded. Simultaneously, corresponding concentrated simulated solutions were prepared according to the proportions of non-volatile components in each working solution. The water content of the simulated solutions was adjusted to match the measured water content at the corresponding yarn moisture removal endpoint by vacuum rotary evaporation. Subsequently, the water activity of the concentrated simulated solutions was measured and recorded. The concentrated simulated solutions were used to evaluate the differences in water activity between different formulation systems under the same water content conditions. Record the mass m0 of the dried yarn before finishing and the mass m1 of the dried yarn after baking and before washing in Example 1 and each comparative example. Then, treat the baked yarn according to the steps described in the corresponding example or comparative example: padding with deionized water at 35°C, neutralizing wash, rinsing with deionized water at 25°C, and drying. Record the mass m2 of the resulting dried yarn. Cut the resulting dried yarn into small pieces and ultrasonically wet them in a mixture of deionized water containing 0.1 mol / L sodium chloride for 30 minutes. Perform potentiometric titration of the titratable carboxyl groups in the system using a 0.05 mol / L sodium hydroxide standard solution, and subtract the blank value from the titration consumption obtained by treating the unfinished blank yarn using the same steps. Calculate the apparent fixation rate of the finishing agent according to the formula: Apparent fixation rate = (m2 - m0) / (m1 - m0) × 100%. The change in titratable carboxyl group content is used to assist in evaluating the fixation of PMVE / MA. Unprocessed PLA / viscose blended yarn of the same specification was used as a blank reference sample. A Fourier transform infrared spectrometer equipped with an attenuated total reflectance accessory was used at 4000 cm⁻¹. -1 Up to 600cm -1 A spectral scan was performed on the yarn of Example 1 after the washing, rinsing, and drying steps in Example 1 within the wavenumber range, with a resolution set to 4 cm⁻¹. -1 A total of 32 scans were performed. After acquisition, the spectral data from Example 1 were subtracted from the blank reference spectrum using spectral processing software, and the results were compared at 1700 cm⁻¹. -1 Up to 1750cm -1 The difference spectrum changes in the carbonyl absorption region are used to help determine the esterification fixation status of PMVE / MA after low-temperature baking.
[0065] The experimental results are shown in Table 2: .
[0066] As shown in Table 2, in Example 1, when the moisture content at the moisture removal endpoint was 6.23%, the yarn water activity was 0.432, the concentrated simulated liquid water activity was 0.418, and the apparent fixation rate was 78.38%. This result indicates that under these moisture removal endpoint conditions, the finishing components in the yarn were in a concentrated state with low water activity, corresponding to a higher apparent fixation rate of the finishing agent.
[0067] The moisture content at the dehumidification endpoint of Comparative Example 5 was 6.38%, close to that of Example 1; however, it did not contain choline chloride, and the yarn water activity was 0.743, while the concentrated simulated solution water activity was 0.736, both higher than that of Example 1, corresponding to an apparent fixation rate of 51.33%. This result shows that, under similar moisture content conditions, the addition of choline chloride has an effect on reducing the water activity of the system; in the absence of choline chloride, the low water activity concentration state is weakened, and the apparent fixation rate of the finishing agent decreases.
[0068] Comparative Example 6, without the addition of glycerol, had a moisture content of 6.15% at the moisture removal endpoint, a yarn water activity of 0.781, a concentrated simulated solution water activity of 0.774, and an apparent fixation rate of 48.24%. Compared to Example 1, Comparative Example 6 showed increased water activity and decreased apparent fixation rate under similar moisture content conditions, indicating that glycerol is beneficial for reducing the water activity of the system and increasing the apparent fixation rate of the finishing agent.
[0069] In Comparative Example 3, the moisture content at the end of the dehumidification process decreased to 0.81%, the yarn water activity was 0.121, the concentrated simulated solution water activity was 0.115, and the apparent fixation rate was 42.58%. These results show that although excessive dehumidification reduced water activity, the corresponding apparent fixation rate was lower than in Example 1. This phenomenon is consistent with the effects of decreased flowability of the finishing components and reduced contact efficiency between PMVE / MA and cellulose hydroxyl groups under excessively low moisture content conditions.
[0070] The moisture content at the end of the dehumidification process in Comparative Example 4 was 19.45%, the yarn water activity was 0.895, the concentrated simulated liquid water activity was 0.887, and the apparent fixation rate was 35.21%. These results indicate that when dehumidification is insufficient, the system remains in a high water activity state, the low water activity concentration environment is not fully formed, and the apparent fixation rate of the finishing agent decreases.
[0071] In ATR-FTIR difference spectrum analysis, after subtracting the baseline background of the untreated PLA / viscose blended yarn, Example 1 showed a difference at 1730 cm⁻¹. -1 Up to 1740cm -1 A new absorption change was observed in the region. Combined with the apparent fixation rate data, this difference spectrum change supports the conclusion that PMVE / MA underwent esterification fixation after low-temperature baking at 120℃. Considering the water activity, apparent fixation rate, and difference spectrum results, Example 1 exhibited a high level of apparent fixation of the finishing agent under suitable free water residue and low water activity conditions.
[0072] Test Example 3: Test objective: To evaluate the effects of polyether compounding and low-temperature fixation processes on the breaking strength, anti-pilling and anti-fuzzing properties, and hydrophilicity retention of PLA / viscose blended yarns, and to examine the retention of finishing effects after multiple standard washes.
[0073] The experimental steps are as follows: The treated yarns from Example 1, Comparative Example 2, and Comparative Example 7, as well as the untreated blank blended yarn, were selected and placed in a standard environment at 20°C and 65% relative humidity for 24 hours to equilibrate. The breaking strength of each group of yarns was measured using a single yarn strength tester. Each sample was randomly tested 20 times and the arithmetic mean was calculated. The single yarn breaking strength was then calculated in conjunction with the yarn linear density. After conditioning, each group of yarns was knitted into plain weft knit fabric on the same single-jersey circular knitting machine with consistent bending depth and tension, ensuring that the weight and areal density of each group of samples were similar. Following the AATCC TM79 test method, deionized water was dropped onto the flat surface of the fabric, and the time required for the water droplet to be completely absorbed and for the specular reflection to disappear was recorded as the water droplet wetting time. Each group of samples was tested 10 times in different areas, and the arithmetic mean was taken. The pilling performance of fabrics was evaluated using the modified Martindale method according to ISO 12945-2. Under a loading pressure of 9 kPa, the samples were rubbed against a standard wool abrasive along a Lissajous trajectory for 10,000 cycles. After the test, the pilling grade of the fabric was evaluated by rating personnel under a standard light source according to the standard rating method, with grades ranging from 1 to 5, where grade 5 was the best. Simultaneously, image analysis was used to count the number of discrete pills within a 100 square centimeter test area on the sample surface as an auxiliary quantitative indicator. Following the ISO 6330 standard washing procedure, each group of knitted fabrics underwent continuous household washing and hanging drying cycles. All samples were subjected to the same washing temperature, detergent, load, mechanical action conditions, and drying method. Fabric samples were collected after 10 and 20 complete washing cycles, readjusted to standard conditions, and then the water droplet wetting time and pilling performance were repeatedly measured and evaluated.
[0074] The experimental results are shown in Table 3: .
[0075] As shown in Table 3, the single yarn breaking strength of Example 1 is 17.63 cN / tex, which is close to the 18.45 cN / tex of the untreated sample, indicating that the yarn breaking strength is well maintained under the treatment conditions of Example 1. After baking at 150℃, the single yarn breaking strength of Comparative Example 7 decreased to 11.24 cN / tex, lower than that of Example 1 and the untreated sample; after 20 washes, the pilling grade of Comparative Example 7 decreased to 2.5, and the number of fuzz balls increased to 29 per 100cm. 2 Compared with Example 1, Comparative Example 7 showed a decrease in single yarn breaking strength and pilling grade after 20 washes, and an increase in the number of fuzz balls, indicating that higher baking temperatures are not conducive to maintaining the mechanical properties of the yarn and the surface properties of the fabric.
[0076] The untreated sample had a wetting time of 2.15 seconds after 0 washes and 2.34 seconds after 20 washes, indicating a relatively fast water absorption rate. However, its pilling grade was 1.5 after 0 washes, which dropped to 1.0 after 20 washes, and the number of pills decreased from 87 per 100cm. 2 Increased to 106 per 100cm 2 This indicates that the untreated sample has poor anti-pilling and anti-fuzzing performance.
[0077] Comparative Example 2: After eliminating the high-humidity pre-distribution step, the number of lint balls after 0 washes was 8 / 100cm. 2 After 20 washes, there are 13 per 100cm. 2 The pilling grades were 4.5 and 4.0 respectively, indicating good anti-pilling performance; however, the wetting time after 0 washes was 21.65 seconds, and after 20 washes it was still 18.14 seconds, longer than in Example 1. This result shows that while eliminating the high-humidity pre-drilling points improves the anti-pilling performance of the fabric surface, it negatively impacts the fabric's water droplet absorption rate.
[0078] In Example 1, the wetting time after 0 washes was 3.42 seconds, and after 20 washes it was 4.18 seconds, remaining within a relatively short time range; its pilling grade after 0 washes was 4.0, and after 20 washes it was 3.5, with the number of lint balls decreasing from 12 / 100cm. 2 Increased to 18 per 100cm 2 The results above show that Example 1 improved the anti-pilling performance of the untreated sample while maintaining good hydrophilicity, and maintained the corresponding effect after 20 standard water washes.
[0079] Test Example 4: Test objective: To evaluate the effect of the high-humidity pre-dip process on the migration of finishing solution to the yarn surface, and to examine the effect of this process on the frictional characteristics of the finished yarn, the uniformity of hydrophilicity along the process, and the removal of water-soluble residues.
[0080] The experimental steps are as follows: The treated yarns from Example 1 and Comparative Example 2, as well as the untreated blank sample, were extracted and placed in a standard environment at 20°C and 65% relative humidity for 24 hours to allow each group of samples to reach equilibrium moisture regain. The dynamic friction coefficient of each group of samples was measured using a yarn friction coefficient meter. During the test, consistent input tension, yarn feed speed, and test length were set. Each group of samples was tested six times, and the arithmetic mean was taken. This index is used to evaluate the change in yarn feed resistance after surface treatment. A test sample was taken at 10-meter intervals along the length of each group of yarns, for a total of 15 samples. These samples were then fabricated into yarn sheets under consistent winding tension and density. The lower end of each yarn sheet was vertically immersed in deionized water, and its vertical capillary wicking height was measured over 5 minutes. The arithmetic mean and coefficient of variation of the 15 test data were calculated. The coefficient of variation was used to evaluate the uniformity of the hydrophilic properties of the treated yarn along its length. Weigh out each group of yarn samples that have undergone appropriate washing, neutralization washing, rinsing and drying conditions; wherein, Example 1 and Comparative Example 2 are processed according to their corresponding process steps, and the unprocessed blank sample is processed according to the washing, neutralization washing, rinsing and drying conditions in step (6) of Example 1, and placed in deionized water at a bath ratio of 1:20, and ultrasonically extracted at a constant temperature of 40°C for 30 minutes. The extract is extracted and cooled to room temperature, and the pH value and conductivity of the water extract are measured using a pH meter and a conductivity meter, respectively. At the same time, the conductivity of the deionized water blank sample is measured as an instrument and water quality reference to evaluate the washing effect of free acid, salt and other water-soluble residues.
[0081] The experimental results are shown in Table 4: .
[0082] Table 4 shows that the coefficient of kinetic friction of the untreated blank sample is 0.246, the wicking height after 5 minutes is 45.3 mm, and the coefficient of variation of wicking height is 2.68%. After treatment, the coefficient of kinetic friction of Example 1 is 0.283, which is higher than that of the untreated blank sample; its wicking height after 5 minutes is 34.6 mm, which is lower than that of the untreated blank sample, but it still maintains a certain short-term wicking capacity. The coefficient of variation of wicking height of Example 1 is 4.15%, which is close to that of the untreated blank sample, indicating that the hydrophilicity of the yarn along the length direction is more uniform after treatment in Example 1.
[0083] In Comparative Example 2, after omitting the high-humidity pre-placement step, the dynamic friction coefficient increased to 0.387, the wicking height decreased to 18.2 mm after 5 minutes, and the wicking height variation coefficient increased to 14.62%. These results show that omitting the high-humidity pre-placement step increases the yarn's running resistance and increases the fluctuation in wicking performance along its length. Compared to Comparative Example 2, Example 1 has a lower dynamic friction coefficient and a smaller wicking height variation coefficient, indicating that the high-humidity pre-placement step is beneficial for improving the surface friction characteristics and hydrophilicity uniformity of the finished yarn.
[0084] Water extraction results showed that the extract from Example 1 had a pH of 6.57 and a conductivity of 11.2 μS / cm, close to the pH of the untreated blank sample (6.82 and conductivity 7.4 μS / cm). The extract from Comparative Example 2 had a pH of 5.34 and a conductivity increased to 43.8 μS / cm, indicating a higher content of water-soluble residues than Example 1. Combining the dynamic friction coefficient, wicking height variation coefficient, and water extraction indices, it can be seen that the high-humidity pre-dip treatment step helps reduce the increase in surface friction of the finished yarn, improves hydrophilicity uniformity along the process, and enhances the removal of water-soluble residues after washing, rinsing, and drying.
[0085] Test Example 5: Test objective: To evaluate the effects of the lactic acid / sodium lactate buffer system, low free water evaporation endpoint, and low-temperature baking process on the mechanical properties of PLA fibers, and to examine the effects of finishing processes on yarn breaking strength, elongation at break, and fabric softness.
[0086] The experimental steps are as follows: The treated yarns from Examples 1, 4, 7, and 8, as well as the untreated blank sample, were selected and placed in a standard environment at 20°C and 65% relative humidity for 24 hours to equilibrate. The breaking strength and elongation at break of each group of yarns were measured using a single yarn strength tester, with the same stretching speed and clamping distance. Each sample was tested independently 20 times, and the arithmetic mean was taken. The single yarn breaking strength was calculated based on the yarn linear density, and the breaking strength retention rate of each group was calculated using the measured values of the untreated blank sample as a benchmark. After moisture conditioning, each group of yarns was knitted into a plain weft knit fabric on the same knitting machine using consistent process parameters. The bending length of the sample was measured using an automatic fabric stiffness tester with the inclined plane method. The bending stiffness of the fabric was calculated by combining the sample surface density, which was used to evaluate the impact of finishing processes on the material's hand feel and softness. Accurately weigh a portion of the blended yarn sample and place it in a stoppered conical flask. Add excess chloroform solvent and dissolve the PLA component at room temperature using magnetic stirring. Filter using a glass frit funnel to remove insoluble viscose fibers and other insoluble residues. Collect the filtrate and concentrate it by rotary evaporation. Then, slowly add methanol to precipitate the PLA. The precipitate is filtered and vacuum dried to obtain the purified PLA sample. All samples were processed under the same dissolution, filtration, precipitation, and drying conditions. Purified PLA was prepared into chloroform solutions of different concentrations, and the outflow time of each concentration was measured using an Ubbelohde viscometer in a 25°C constant temperature water bath. The intrinsic viscosity was calculated by extrapolation, based on the Mark-Houwink equation [η] = K·M under the same solvent system and test temperature. αCalculate the viscosity-average molecular weight of PLA, where M represents the viscosity-average molecular weight of PLA, and K is taken as 1.29 × 10⁻⁶. -4 The α value was set to 0.82, and the same K and α values were used in the calculations for all sample groups. The viscosity-average molecular weight retention rate of PLA was calculated based on the untreated blank sample.
[0087] The experimental results are shown in Table 5: .
[0088] Table 5 shows that the breaking strength of the untreated blank sample yarn is 18.45 cN / tex, and the viscosity-average molecular weight of PLA is 8.42 × 10⁻⁶. 4 g / mol. In Example 1, after finishing, the single yarn breaking strength was 17.63 cN / tex, with a breaking strength retention rate of 95.5%; the PLA viscosity-average molecular weight was 8.16 × 10⁻⁶. 4 The molecular weight retention rate was 96.9% (g / mol); the fabric bending stiffness increased from 15.62 μN·m to 18.27 μN·m. These data indicate that under the finishing conditions of Example 1, the yarn breaking strength, PLA viscosity-average molecular weight, and fabric softness were maintained at a high level.
[0089] Comparative Example 4 had a higher residual free water content at the end of the dehumidification process, with a single yarn breaking strength retention rate of 77.8%, PLA viscosity-average molecular weight retention rate of 77.5%, breaking elongation of 8.54%, and fabric bending stiffness of 21.46 μN·m. Compared with Example 1, Comparative Example 4 showed a decrease in both breaking strength retention rate and molecular weight retention rate, indicating that the increased residual free water content before the baking step reduced the retention of PLA components and yarn mechanical properties.
[0090] Comparative Example 7, baked at 150℃, exhibited a single yarn breaking strength retention rate of 60.9%, a PLA viscosity-average molecular weight retention rate of 58.9%, a breaking elongation of 6.13%, and a fabric bending stiffness of 27.85 μN·m. Compared to Example 1, Comparative Example 7 showed a decrease in PLA viscosity-average molecular weight retention rate and yarn breaking strength retention rate, while exhibiting an increase in fabric bending stiffness.
[0091] Comparative Example 8, without the addition of L-lactic acid and sodium L-lactic acid, used hydrochloric acid to adjust the initial pH to 3.8. Its single yarn breaking strength retention rate was 82.4%, and its PLA viscosity-average molecular weight retention rate was 81.2%, both lower than that of Example 1. Under the same initial pH conditions, the PLA viscosity-average molecular weight retention rate and yarn breaking strength retention rate of Example 1 were higher than those of Comparative Example 8, indicating that the lactic acid / sodium lactate buffer system has an improving effect on the above indicators.
[0092] Based on the combined data of breaking strength, breaking elongation, fabric bending stiffness, and PLA viscosity-average molecular weight, Example 1 exhibited high PLA viscosity-average molecular weight retention and yarn mechanical property retention under the conditions of low free water evaporation endpoint, lactic acid / sodium lactate buffer system, and low-temperature baking at 120℃.
[0093] Test Example 6: Test objective: To evaluate the skin contact safety and physicochemical comfort index of finished blended yarn fabrics, and to provide a test basis for describing the skin-friendliness of materials.
[0094] The experimental steps are as follows: The treated yarns from Examples 1, 2, and 8, as well as the untreated blank sample, were extracted. The untreated blank sample was treated according to the washing, neutralizing, rinsing, and drying conditions in step (6) of Example 1, and then knitted into plain weft knitted fabrics of the same specifications. The free and hydrolyzed formaldehyde content in the fabrics was tested according to the standard method of GB / T 2912.1. The sample was weighed and placed in a constant temperature water bath for extraction. The absorbance was measured at a wavelength of 412 nm using the acetylacetone colorimetric method combined with a spectrophotometer. The formaldehyde content was calculated, and the detection limit was 20 mg / kg. The pH value of the fabric aqueous extract was tested according to the standard method of GB / T 7573. After the sample was cut into small pieces, it was added to deionized water containing 0.1 mol / L potassium chloride. After mechanical shaking at room temperature for 2 hours, the pH value of the extract was measured using a precision pH meter. Each group was tested in parallel 3 times and the arithmetic mean was taken. Odor evaluation shall be conducted in accordance with the odor criteria in GB 18401, and the presence of musty odor, high-boiling-point petroleum odor, fishy odor or aromatic hydrocarbon odor shall be recorded. The content of decomposable carcinogenic aromatic amine dyes was tested according to the standard method of GB / T 17592. The samples were treated by reduction pyrolysis, extracted and concentrated, and then qualitatively and quantitatively analyzed by gas chromatography-mass spectrometry. The detection limit was 20 mg / kg.
[0095] The experimental results are shown in Table 6: .
[0096] Note: "Not detected" in the table means that the test result is below the detection limit of the corresponding method; the detection limit for formaldehyde and decomposable carcinogenic aromatic amine dyes in this test is 20 mg / kg.
[0097] As shown in Table 6, after finishing, corresponding washing, rinsing, and drying steps, no free and hydrolyzed formaldehyde or decomposable carcinogenic aromatic amine dyes were detected in Examples 1 and 2, and the odor evaluation result was odorless. The pH value of the aqueous extract of the fabric in Example 1 was 6.4, and that in Example 2 was 6.6, both close to neutral and within the pH limit range of 4.0 to 8.5 specified in GB 18401 for textile products in direct contact with skin (Class B).
[0098] Comparative Example 8 did not use a lactic acid and sodium lactate buffer system in the preparation of the finishing solution; hydrochloric acid was used directly to adjust the initial pH value. Although formaldehyde and decomposable carcinogenic aromatic amine dyes were also not detected, and the odor evaluation result was odorless, the pH value of the aqueous extract of the final finished fabric was 4.7, lower than that of Examples 1 and 2, and close to the lower limit of the pH limit for textile products (Class B) that come into direct contact with the skin as specified in GB 18401. Compared with Comparative Example 8, the pH values of the aqueous extracts of Examples 1 and 2 were closer to neutral, indicating that the lactic acid / sodium lactate buffer system helps improve the pH retention of the fabric after washing, rinsing, and drying.
[0099] The test data from Examples 1 and 2 show that after finishing, corresponding washing, rinsing, and drying steps, free and hydrolyzed formaldehyde and decomposable carcinogenic aromatic amine dyes were not detected in the samples. The odor evaluation result was odorless, and the pH value of the water extract was within the corresponding limit range for textile products that come into direct contact with the skin. The above results can serve as supplementary evidence for the skin contact safety and physicochemical affinity of the material.
[0100] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A biodegradable, skin-friendly, and moisture-wicking corn fiber blended yarn material, characterized in that, The biodegradable, skin-friendly, and moisture-wicking corn fiber blended yarn material is made from corn fiber blended yarn through finishing solution padding, moisture removal, and baking; based on the preparation of 1L of final finishing solution, the finishing solution is made from raw materials containing the following weights: Choline chloride 18-22g; L-lactic acid 20-25g; 4-6g of L-sodium lactate; Glycerol 5-8g; Poloxamer 188 9-12g; 3–4 g of thermally responsive cloud point-adjusting block copolymer; An aqueous solution of poly(methyl vinyl ether-alternative-maleic acid) with a mass fraction of 10wt% to 15wt% is added such that the PMVE / MA content in the solution is 25 to 35g based on the dry basis of the anhydride-type PMVE / MA raw material. 3-5g of magnesium chloride hexahydrate; Bring the volume of deionized water to 1L.
2. The biodegradable, skin-friendly, and moisture-wicking corn fiber blended yarn material according to claim 1, characterized in that, The corn fiber blended yarn is a blended yarn of polylactic acid fiber and viscose fiber, and the mass ratio of polylactic acid fiber to viscose fiber is 65-75:25-35.
3. The biodegradable, skin-friendly, and moisture-wicking corn fiber blended yarn material according to claim 1, characterized in that, The thermally responsive cloud point regulating block copolymer is selected from polyoxypropylene-polyoxyethylene-polyoxypropylene type reverse triblock copolymer or polyoxyethylene-polyoxypropylene-polyoxyethylene type intermediate cloud point triblock copolymer. The average molecular weight of the thermally responsive cloud point regulating block copolymer is 1900-2000, the mass fraction of polyoxyethylene segments in the thermally responsive cloud point regulating block copolymer is 50 wt%, and the cloud point of the thermally responsive cloud point regulating block copolymer is 69-73℃ when measured alone.
4. The biodegradable, skin-friendly, and moisture-wicking corn fiber blended yarn material according to claim 1, characterized in that, Based on the preparation of 1L of final finishing solution, the finishing solution is made from raw materials containing the following by weight: 20g choline chloride, 22g L-lactic acid, 5g sodium L-lactic acid, 6g glycerol, 10g poloxamer 188, 4g thermally responsive cloud point adjusting block copolymer, 250g of 12wt% poly(methyl vinyl ether-alternative-maleic acid) aqueous solution, 4g magnesium chloride hexahydrate, and deionized water to a final volume of 1L.
5. The biodegradable, skin-friendly, and moisture-wicking corn fiber blended yarn material according to claim 1, characterized in that, The poly(methyl vinyl ether-alternating-maleic acid) aqueous solution was prepared by the following steps: The polymethyl vinyl ether-alternating-maleic anhydride powder was divided into five equal batches. Under mechanical stirring conditions of 250-400 r / min, each batch of the polymethyl vinyl ether-alternating-maleic anhydride powder was added to deionized water in sequence. After the previous batch of polymethyl vinyl ether-alternating-maleic anhydride powder was wetted by deionized water and there was no floating dry powder or obvious agglomerates, the next batch of polymethyl vinyl ether-alternating-maleic anhydride powder was added. After all five batches of polymethyl vinyl ether-alternating-maleic anhydride powder were added, stirring was continued for 10 min to obtain a suspension. The suspension is heated to 85–95°C in a covered but not sealed container, and the temperature is maintained at 85–95°C while stirring continuously at a speed of 250–400 r / min for 2–4 hours. Heating is stopped after the suspension is transformed into a homogeneous solution without visible solid particles and without stratification. The homogeneous solution was cooled to 25°C at a stirring speed of 100–200 r / min. The total mass of the homogeneous solution was weighed, and deionized water was added to make up to the predetermined total mass. The solution was filtered through a filter screen and allowed to stand to remove bubbles until no visible bubbles were visible, thus obtaining the poly(methyl vinyl ether-alternative-maleic acid) aqueous solution.
6. A method for preparing a biodegradable, skin-friendly, and moisture-wicking corn fiber blended yarn material according to any one of claims 1-5, characterized in that, Includes the following steps: S1. Prepare the raw materials to prepare the finishing solution, and adjust the pH value of the finishing solution to 3.6-4.0; S2. Immerse the corn fiber blended yarn in the finishing solution and perform a two-dip and two-padding process to control the liquid content of the corn fiber blended yarn to be 65% to 75% to obtain the padded yarn. S3. The impregnated yarn is introduced into a temperature and humidity control zone for humidity control and dwell treatment to obtain pretreated yarn. S4. The pretreated yarn is introduced into a hot air drying room for hot air penetration treatment to remove moisture, and the dehumidified yarn is obtained. S5. The dehumidified yarn is directly introduced into a baking oven without being washed with water, and baked at 115-125℃ for 3-4 minutes to obtain the baked yarn. S6. The baked yarn is washed and neutralized, rinsed and dried to obtain the biodegradable, skin-friendly and moisture-wicking corn fiber blended yarn material.
7. The method for preparing the biodegradable, skin-friendly, and moisture-wicking corn fiber blended yarn material according to claim 6, characterized in that, The specific implementation method of step S1 is as follows: Choline chloride, L-lactic acid, sodium L-lactic acid, and glycerol are added sequentially to deionized water and stirred until homogeneous. The pH of the first mixture is then adjusted to 3.6–4.0 using an aqueous solution of L-lactic acid or sodium L-lactic acid to obtain the second mixture. Poloxamer 188 and thermally responsive cloud point adjusting block copolymer were added to the second mixture and stirred until homogeneous. Then, poly(methyl vinyl ether-alternative-maleic acid) aqueous solution was added to obtain the third mixture. At 25°C and under continuous stirring, a magnesium chloride aqueous solution containing magnesium chloride hexahydrate was injected into the third mixture at a rate of 10 mL / min using a peristaltic pump. Stirring continued, and deionized water was added to bring the volume to 1 L to obtain the finishing solution.
8. The method for preparing the biodegradable, skin-friendly, and moisture-wicking corn fiber blended yarn material according to claim 6, characterized in that, In step S3, the ambient temperature of the temperature and humidity control zone is controlled at 63-68℃, the relative humidity is controlled at 90%-95%, the residence time is 45-60s, and the water loss of the impregnated yarn in the temperature and humidity control zone is controlled to be 8%-12% of the initial liquid content of the impregnated yarn.
9. The method for preparing the biodegradable, skin-friendly, and moisture-wicking corn fiber blended yarn material according to claim 6, characterized in that, In step S4, the processing temperature of the hot air drying chamber is 90-95°C. When the residual free water content of the dehumidified yarn drops to 5%-8% on a dry basis, the dehumidified yarn is led out of the hot air drying chamber.
10. The method for preparing the biodegradable, skin-friendly, and moisture-wicking corn fiber blended yarn material according to claim 6, characterized in that, The specific implementation method of step S6 is as follows: the baked yarn is rinsed with deionized water at 35°C for 1 minute, then the rinsed yarn is immersed in a sodium bicarbonate aqueous solution at 35°C, pH 7.0 and mass concentration of 0.2-0.5 g / L for 2 minutes, rinsed with deionized water at 25°C for 60 seconds, and dried at 80-90°C.